2002
DOI: 10.1006/viro.2002.1483
|View full text |Cite
|
Sign up to set email alerts
|

Surface Features of Potato Virus X from Fiber Diffraction

Abstract: Fiber diffraction patterns have been obtained from oriented sols of potato virus X. Orientation in the sols was greatly improved by a combination of centrifugation and exposure to very high magnetic fields. Diffraction patterns were also improved by using a very finely collimated synchrotron X-ray beam. The diffraction patterns show that there are 8.9 subunits in each turn of the viral helix and that intersecting sets of deep grooves mark the viral surface, with one set running almost longitudinally and the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 18 publications
4
52
1
Order By: Relevance
“…Mexican. PVX was purified (Parker et al, 2002) from Nicotiana clevelandii. The inoculum for PVX-D21 was a gift from Dr Simon Santa Cruz (Scottish Crop Research Institute, Dundee, Scotland, UK), made by deleting residues 2-22 from PVX (Chapman et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mexican. PVX was purified (Parker et al, 2002) from Nicotiana clevelandii. The inoculum for PVX-D21 was a gift from Dr Simon Santa Cruz (Scottish Crop Research Institute, Dundee, Scotland, UK), made by deleting residues 2-22 from PVX (Chapman et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…The inoculum for PVX-D21 was a gift from Dr Simon Santa Cruz (Scottish Crop Research Institute, Dundee, Scotland, UK), made by deleting residues 2-22 from PVX (Chapman et al, 1992). The mutant virus was purified (Parker et al, 2002) from N. clevelandii. All of the potexvirus purifications included the addition of protease inhibitors (Parker et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All potexviruses are believed to share a common architecture, with slightly less than 9 protein subunits per helical turn (55). More-precise fiber diffraction studies (52) found the helical symmetry of PVX to be 8.9 protein subunits per turn and the helical pitch to be 34.5 Å. The virion was shown to have a deeply grooved surface.…”
mentioning
confidence: 99%
“…For example, attempts to resolve the atomic structure of Potato virus X (PVX, genus Potexvirus) by X-ray fibre diffraction, while revealing some features of PVX virions, generally failed (Parker et al, 2002). Cryoelectron microscopy of PVX confirmed the previously determined helix characteristics and provided information on structural features of the virion surface, but could generate the structure only at a relatively low resolution of 14 Å (Kendall et al, 2008).…”
Section: Progress In Structural Studies Of Helical Virusesmentioning
confidence: 99%